Afghan Refugees in Pakistan, Forced Repatriation, and its Consequences (Salam International Academic Journal, 2023)
This brief article attempts to provide an overview of the historical and current situation of Afghan refugees in Pakistan in terms of quantity and quality through accredited statistics. In October 2023, the interim Pakistani government decided to immediately deport 1.7 million Afghan refugees who, it claims, lack legal documentation. The researcher discusses the motives behind the hasty and ill-timed forced repatriation of Afghan refugees, considering the unsuitable weather in both the origin and host countries. The study concludes that the Pakistani government’s decision to deport Afghan refugees is a political and security decision, not directly related to the refugees’ own circumstances. The article analyzes both positive and negative reactions within Pakistan and internationally to the deportation process, indicating that overall, the level of criticism and opposition to this action by the Pakistani government is more intense than approval and consent. The article concludes with a discussion on the humanitarian implications of forced repatriation and its effects on the relations between the two countries, showing that the action will likely lead to further deterioration in Kabul-Islamabad relations across various sectors. Finally, the article presents suggestions for the relevant authorities to properly address the issue of refugees and returnees.
Keywords: Afghan refugees; forced repatriation; Commissionerate for Afghan refugees in Pakistan